#3CityLink: Disrupting Learning through a Translocal Art Pedagogy Exchange Project. (23rd September 2018) - Wimpenny, Katherine; Knowles, Rachelle Viader; Ramsay, Christine; Speculand, Jacqui
Abstract: #3CityLink involved fine arts researchers, artists and students in three cities: Regina, Canada; Coventry, UK; and Gyumri, Armenia. The project presented a platform for translocal creative interactions using online screen‐based media and on‐the‐ground dialogues. Artists and students investigated the concerns of their locale, questioning the role of the artist in building narratives, revealing lost histories and imagining the future of where they live. Using descriptive case study design, the findings present the opportunities for enriching the student learning experience through challenging habitual approaches to art production, through alternative approaches to digital pedagogy in art education. Students' artwork took on new dimensions beyond what they could have produced working in relative isolation in a university‐only studio setting. Students were encouraged to pursue and persist in online learning spaces whilst also taking responsibility for organising their own learning and that of others. Nonetheless, using visual technology and social media for connected, artistic, co‐investigation needs further refinement to engage learners, and enhance the quality of visual presence and its potential in open education.